Hydrolyzed rice bran as source of lipids and solid acid catalyst during in situ (trans)esterification. Issue 2 (17th February 2020) - Sutanto, Sylviana; Go, Alchris Woo; Ismadji, Suryadi; Ju, Yi-Hsu
ABSTRACT: Dilute acid hydrolysis is commonly used to break down polysaccharides in biomass into fermentable sugars. Some biomass, like rice bran (RB), contains lipids, which are found to remain and become concentrated in the residual biomass matrix after hydrolysis. Unfortunately, these residues are often left unexplored. In this work, lipid contained in residues recovered after dilute acid hydrolysis of RB was further subjected to in situ (trans)esterification with methanol under subcritical conditions. (Trans)esterification was carried out using different solvent-to-solid ratios (4 to 6 mL/g), temperatures (100 to 250°C), time, and reactor loading (57 to 66% v/v). The highest FAME (Fatty Acid Methyl Ester) yield and conversion were obtained at 165°C with a short reaction time. Hydrolyzed RB acted as both feedstock and acid catalyst considering the lipid it contains (∼48% w/w) and the acid sites (1.63 ± 0.05 mmol SO3 H)/g dry hydrolyzed-RB). The sulfonic acid group was quantified and determined via a titrimetric method, and verified with Fourier Transform Infra Red (FTIR) analysis. This study provides insights into the possible synthesis of a green solid acid catalyst as co-product during acid hydrolysis of polysaccharides in agricultural residues, and the possible use of lipid-containing biomass as feedstock in (trans)esterification processes, leading to a better utilization of agricultural residue.